Characterization of nonalcoholic fatty liver disease unrelated to the metabolic syndrome - YILMAZ, YUSUF (WILEY, 2012)
Background Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of the metabolic syndrome (MS). However, not all patients with the MS will develop NAFLD and not all patients with NAFLD have the MS. We sought to investigate the differences between patients with biopsy-proven NAFLD with and without the MS. Methods A total of 357 consecutive patients with biopsy-proven NAFLD were analysed. Of them, 216 patients had nonalcoholic steatohepatitis (NASH) and 96 a fibrosis score = 2. The MS was defined as = 3 of the ATP III criteria. Results A total of 214 patients with NAFLD met the criteria for the MS, while the remaining 143 did not. In NAFLD patients with the MS, homeostasis model of insulin resistance (P = 0.03; OR, 1.06; 95% CI, 1.0231.25 per unit increase) and diabetes (P = 0.01; OR, 1.2; 95% CI, 1.12.4) were independent predictors of NASH. In NAFLD patients without the MS, the only variable independently associated with NASH was haemoglobin (P = 0.007; OR, 1.9; 95% CI, 1.43.6 per 50 g/L increase). Alanine aminotransferase (P = 0.03; OR, 1.04; 95% CI, 1.0061.11 per 10 U/L increase) was an independent predictor of fibrosis = 2 in NAFLD patients with the MS, while haemoglobin (P = 0.02; OR, 1.4; 95% CI, 1.21.9 per 50 g/L increase) was the only variable significantly associated with fibrosis = 2 in NAFLD patients without the MS. Conclusions Increased haemoglobin in NAFLD subjects without MS should be considered in the selection of cases for histological assessment.
Keywords: Fibrosis; haemoglobin; insulin resistance; nonalcoholic steatohepatitis; STEATOHEPATITIS; HEMOGLOBIN; DIAGNOSIS; PATHOGENESIS; ASSOCIATION; POPULATION; PREVALENCE; GUIDELINES